Subcutaneous adipocyte diameter variations during lactation in sheep - Piasentier E.; Bovolenta S.; Filacorda S.; Susmel P. (Body condition of sheep and goats: Methodological aspects and applications, 1995)
Results are presented for measurements made on 12 lactating Bergamasa ewes and a further 6 dry ewes which grazed together. The lactating ewes had been separated into 2 groups in the first half of pregnancy and fed differently. During this period, from an initial body condition score of 3.0 units, one group (MBC) gained 0.4 points and the other (LBC) lost 0.25 points. Samples of subcutaneous adipose tissue were removed from the rump by human biopsy syringe 3, 11, 21, and 43 days after lambing to determine the average adipocyte diameter. At the same time, the ewes were body scored. The dry ewes (NL) were examined on the first and third measurement day. Both groups of lactating ewes lost body condition, measured both in terms of body score and adipocyte diameter, while the NL ewes maintained their condition. The absolute variation of D was higher in the ewes in group MBC. The adipocyte diameter allowed the identification of a phase of rapid fat mobilization during the first 11 days of lactation. The cell diameter contributed more than BCS to the overall discrimination between clusters of different body condition.
Seminar of the Working Group on Body Condition of Sheep and Goats of the FAO/CIHEAM Network on Sheep and Goats, 24-31 Mar 1994, Zaragoza (Spain)